Realizing Simbatan - Magetan As A Tourist Village: Utopia and Realita - Mulyati, Tatik; Rohmatiah, Ahadiati; Haryani, Anik T.; Susilo, Hendro (Universitas Nusantara PGRI Kediri, 2021)
Simbatan Village in Magetan has nature tourism, historical, cultural tourism, and Dewi Sri's cultural heritage site called Candi Simbatan, but it has not been managed optimally. This village also has quite a lot of people with disabilities with poor socio-economic conditions. In realizing the tourism village, Simbatan has problem, namely: does not master plan yet, food court, pedestrians in tourist locations that were still in the form of land, places for people with disabilities did not exist and their products were splashed batik and marketing collided. Solutions are carried out in stages, namely: making a master plan; improve infrastructure at tourist sites. In line with these efforts, solutions for persons with disabilities are: improvement of workshop shelters; skills training and production of goods as well as assisting with marketing. The aim of this activity is to combine the existing tourism potential with the activities and work of people with disabilities so that their welfare and independence can increase. The integration is carried out gradually and continuously to create a tourist village.